2022
DOI: 10.1037/pag0000663
|View full text |Cite
|
Sign up to set email alerts
|

Relative effectiveness of general versus specific cognitive training for aging adults.

Abstract: In the present study, we examined three experimental cognitive interventions, two targeted at training general cognitive abilities and one targeted at training specific instrumental activities of daily living (IADL) abilities, along with one active control group to compare benefits of these interventions beyond expectation effects, in a group of older adults (N = 230). Those engaged in general training did so with either the web-based brain game suite BrainHQ or the strategy video game Rise of Nations, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…However, it is possible that a worse long-term impact might have been observed overall if a longer follow-up was used, such as 1 year. A recent study assessing cognitive training for older adults found that little or no benefit remained 1 year after intensive initial training [63]. This study's findings suggest a need for resources to provide continuous training or periodic boosting given that benefits gained from pre-to posttest measurement dropped after 6 months.…”
Section: Longitudinal Effectsmentioning
confidence: 66%
“…However, it is possible that a worse long-term impact might have been observed overall if a longer follow-up was used, such as 1 year. A recent study assessing cognitive training for older adults found that little or no benefit remained 1 year after intensive initial training [63]. This study's findings suggest a need for resources to provide continuous training or periodic boosting given that benefits gained from pre-to posttest measurement dropped after 6 months.…”
Section: Longitudinal Effectsmentioning
confidence: 66%
“…The interventions mainly aim at re-establishing or reinforcing the previously learned skills which include repeated exercise of tasks, increasing in complexity, and those targeting certain cognitive domains, developing compensatory strategies for cognitive deficits such as use of electronic memory devices, calendars and alarms, and/or facilitating adaptation to irremediable cognitive impairments (Koehler et al, 2012).Cognitive communication rehabilitation includes the parameters of general interventions which target a range of cognitive processes, and cognitive specific interventions which target a specific cognitive process such as memory or attention (Sanjuán et al, 2020;Gray et al, 2022). Much remains to be learned about the kinds of training programmes that provide meaningful changes beyond the specific skills trained.…”
Section: Discussionmentioning
confidence: 99%
“…Timed Instrumental Activities of Daily Living (TIADL) [13,[34][35][36], The Everyday Problem Test (EPT) [13,35,37], The Activities of Daily Living Questionnaire (ADL) [31], the Chinese version of the Observed Task of Daily Living (OTDL-C) [38], and the Clinical Dementia Rating-Sum of Boxes (CDR-SOB) [32] are all commonly used in assessing cognitive function in older adults. The IADL scale [31,[39][40][41][42][43], ECB test [26,27], Barthel Index [42], OTDL tasks [37], Chula ADL index [44], EPCCE [25], and DAFS [25] were utilized. The most employed were the IADL scale and its timed version, the TIADL.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%